81 Development of adverse cardiac remodelling in experimental diabetes is regulated by endothelial NOX4 nadph oxidase. (June 2018) - Edgar, Kevin S; Gill, Eleanor; Patterson, Ellen; Hargey, Ciarán; Grieve, David
Abstract : Background: The characteristic structural and functional cardiac abnormalities which occur in diabetes, including fibrosis, inflammation and microvascular remodelling, and result in increased susceptibility to cardiovascular stress are largely mediated by reactive oxygen species (ROS) generation. In this study we aimed to investigate the specific contribution of endothelial Nox4 NADPH oxidase, a major source of cardiovascular ROS, to adverse cardiac remodelling in experimental diabetes. Methods: Diabetes was induced in gene-modified mice with endothelial-specific Nox4 overexpression (Tg) and wild-type (WT) littermate controls (10–12 weeks old; n=8–12 per group) by streptozotocin injection (STZ, 50 mg/kg i.p. for 5 consecutive days). After 6 months, analyses of cardiac function (echocardiography), glucose metabolism (blood glucose, HbA1c) and myocardial gene expression (qPCR) were performed. Results: Endothelial Nox4 overexpression had no effect on blood glucose or HbA1c levels in control or diabetic Tg animals. Tg control mice demonstrated impaired basal diastolic function (E/A ratio: WT 1.6±0.09 vs Tg 1.4±0.08, p<0.05) which was not affected by experimental diabetes, whilst WT STZ mice showed significant diastolic dysfunction versus controls (E/A ratio: control 1.6±0.09 versus STZ 1.3±0.04, p<0.05). Systolic function remained similar between groups. Consistent with these functional data, CTGF and MMP2 expression were increased (p<0.05) in Tg control animals, but were not affected by STZ, whereas CTGF was elevated in WT STZ animals versus controls (p<0.05). Expression of eNOS (p<0.05) and CD31 (p<0.01) was also increased in Tg versus WT controls suggestive of vascular remodelling. Interestingly, expression of antioxidant genes in response to STZ diabetes was more highly increased in Tg versus WT animals (compared to controls, p<0.05): SOD1 (WT 31±6.3%, Tg 78±24%), SOD2 (WT 37±10%, Tg 63±23%), PRDX1 (WT 55±14%, Tg 139±68%) and catalase (WT 24±14%, Tg 85±28%). This may at least partly explain protection of Tg STZ animals against further diastolic dysfunction. Conclusion: Taken together, these data indicate that while increased endothelial Nox4 expression may impair basal cardiac function, it protects against adverse cardiac remodelling and dysfunction seen in experimental diabetes, via modification of key antioxidant signalling pathways, thus highlighting a key role for this major Nox isoform in the diabetic heart.